Amino acids transitioning of 2009 H1N1pdm in Taiwan from 2009 to 2011. - Guang-Wu Chen (Public Library of Science (PLoS), 2012)
A swine-origin influenza A was detected in April 2009 and soon became the 2009 H1N1 pandemic strain (H1N1pdm). The current study revealed the genetic diversity of H1N1pdm, based on 77 and 70 isolates which we collected, respectively, during the 2009/2010 and 2010/2011 influenza seasons in Taiwan. We focused on tracking the amino acid transitioning of hemagglutinin (HA) and neuraminidase (NA) genes in the early diversification of the virus and compared them with H1N1pdm strains reported worldwide. We identified newly emerged mutation markers based on A/California/04/2009, described how these markers shifted from the first H1N1pdm season to the one that immediately followed, and discussed how these observations may relate to antigenicity, receptor-binding, and drug susceptibility. It was found that the amino acid mutation rates of H1N1pdm were elevated, from 9.29×10(-3) substitutions per site in the first season to 1.46×10(-2) in the second season in HA, and from 5.23×10(-3) to 1.10×10(-2) in NA. Many mutation markers were newly detected in the second season, including 11 in HA and 8 in NA, and some were found having statistical correlation to disease severity. There were five noticeable HA mutations made to antigenic sites. No significant titer changes, however, were detected based on hemagglutination inhibition tests. Only one isolate with H275Y mutation known to reduce susceptibility to NA inhibitors was detected. As limited Taiwanese H1N1pdm viruses were isolated after our sampling period, we gathered 8,876 HA and 6,017 NA H1N1pdm sequences up to April 2012 from NCBI to follow up the dynamics of mentioned HA mutations. While some mutations described in this study seemed to either settle in or die out in the 2011-2012 season, a number of them still showed signs of transitioning, prompting the importance of continuous monitoring of this virus for more seasons to come.